A cross-sectional analysis of the urine microbiome of children with neuropathic bladders. Issue 5 (October 2020) - Forster, Catherine S.; Panchapakesan, Karuna; Stroud, Crystal; Banerjee, Payal; Gordish-Dressman, Heather; Hsieh, Michael H.
Summary: Background: Distinguishing a urinary tract infection (UTI) from asymptomatic bacteriuria (ASB) in children with neuropathic bladders is difficult. Currently used markers of infection, such as the routine urinalysis, lack specificity for UTI in this population. The urinary microbiome may help differentiate these states. Objective: The objective of this work was to describe the baseline microbiome in children with neuropathic bladders, and to determine if differences exist among the urine microbiomes of children with neuropathic bladders who have negative urine cultures, ASB, or UTI. Study design: This is a cross-sectional study of children with neuropathic bladders who use clean intermittent catheterization for bladder management who had a urine culture sent as part of clinical management. Residual urine, initially collected via catheter for urine culture, was obtained for use in this work. Microbial DNA was isolated, and the V4 region of the 16SrRNA gene sequenced. The relative abundance of each bacteria was measured in each group. Alpha diversity, measured by Chao1 and the Shannon Diversity Index, was also measured in each group. PERMANOVA was used to compare the microbiota between groups. Results: 36 children with neuropathic bladders were included in this study (UTI = 11, ASB = 19, negative cultures = 4). The most abundant bacteria were unspecified Enterobacteriaceae, Klebsiella, Staphylococcus, Streptococcus, and Enterococcus. Children who catheterize their urethra have a higher proportion of Staphylococcus, while the urine microbiome of those who catheterize through a Mitrofanoff consists predominantly of members of the family Enterobacteriaceae . Given the low numbers of patients with Mitrofanoffs and augmented bladders, we did not statistically compare the urine microbiomes between these patients. There was no difference in either alpha diversity or the overall microbiota between children with neuropathic bladders with UTI, ASB, and negative cultures. Discussion: In this pilot cohort of children with neuropathic bladders, bacteria that are members of the family Enterobacteriaceae are the most predominant bacteria in the urine microbiomes. There was no difference in the urine microbiome between those with UTI, ASB, and negative cultures. Route of catheterization may affect the composition of the urine microbiome, although due to limited sample size, this was not confirmed statistically. Conclusion: There was no difference in the urine microbiome between patients with negative urine cultures, ASB, and UTI. Further work is needed to determine if the urine microbiome varies based on either the route of catheterization or the presence of augmented bladder. Summary Figure Principal coordinate analysis chart demonstrating a lack of clustering between patients with no growth, asymptomatic bacteriuria (ASB), and urinary tract infection (UTI). Summary Figure